2020
DOI: 10.1115/1.4048509
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dissolved Cavern on the Fracture Propagation in Vuggy Carbonate Reservoir

Abstract: The acid-fracturing is applied wildly to simulate the formation in vuggy carbonate reservoirs. But it does not figure out clearly the mechanism of fracture propagation while fracture encountering dissolved cavern and there are few researches considering the influence of dissolved cavern on fracture propagation. In order to study fracture propagation regularity in vuggy carbonate reservoirs, numerical simulations are carried out by the seepage-stress-damage coupling equation based on the damage mechanics theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…It is of great significance to explore and investigate the core action mechanism of the typical fracture propagation and to consider the effect of the karst cave on fracture propagation for optimizing the fracturing scheme and improving the probability of fracturecave connection in a carbonate reservoir. To deeply study the fracture development law of the carbonate reservoir, Guo et al [26] combined with the damage mechanics theory and carried out the numerical simulation through the seepage-stress-damage coupling equation; the accuracy of the numerical simulation was verified by the experimental results. The results show that there are four types of crack propagation, including block, direct span, cross after deflection, and deflection.…”
Section: Introductionmentioning
confidence: 99%
“…It is of great significance to explore and investigate the core action mechanism of the typical fracture propagation and to consider the effect of the karst cave on fracture propagation for optimizing the fracturing scheme and improving the probability of fracturecave connection in a carbonate reservoir. To deeply study the fracture development law of the carbonate reservoir, Guo et al [26] combined with the damage mechanics theory and carried out the numerical simulation through the seepage-stress-damage coupling equation; the accuracy of the numerical simulation was verified by the experimental results. The results show that there are four types of crack propagation, including block, direct span, cross after deflection, and deflection.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al [5] conducted experiments to investigate the effect of vugs on hydraulic fracture propagation by using true triaxial apparatus and identified three main interaction modes; that is, the hydraulic fracture may cross, bypass, or be arrested by the vug. Guo et al [6] carried out a numerical simulation to examine the effect of dissolved cavern on hydraulic fracture by using the seepage stress damage coupling model, and some influencing factors including cavern property, reservoir parameter, and treatment parameters were analyzed. Luo et al [7,8] presented numerical simulation to investigate the effect of caverns on hydraulic fracture propagation direction under triaxial stress condition based on the extended finite element method and concluded that fractures tend to deflect from the maximum horizontal principal stress direction due to caverns.…”
Section: Introductionmentioning
confidence: 99%